Investigating the Hemodynamic Changes in Stenosed Arteries with and without Catheter Insertion - Kuldeep Maurya, (International Journal of Scientific Research in Science and Technology, 2024)
The study of hemodynamics in stenosed arteries is critical for understanding cardiovascular diseases and optimizing treatment strategies. This research explores the hemodynamic alterations caused by arterial stenosis and examines the influence of catheter insertion on these dynamics. Using mathematical modeling and computational fluid dynamics, the study evaluates key parameters such as wall shear stress, pressure drop, and flow velocity profiles under varying conditions. Results highlight significant differences in hemodynamic behavior with and without catheter insertion, emphasizing the implications for clinical practices such as catheter-based interventions.
Keywords: Hemodynamics; stenosed arteries; catheter insertion; blood flow dynamics; wall shear stress; pressure gradient; cardiovascular biomechanics